2016
DOI: 10.1177/0194599816679941
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Likelihood of Voice Therapy Attendance: Report from the CHEER Network

Abstract: Objective To identify factors associated with the likelihood of attending voice therapy among patients referred for it in the CHEER (Creating Healthcare Excellence through Education and Research) practice-based research network infrastructure. Study Design Prospectively enrolled cross-sectional study. Setting CHEER network of community and academic sites. Methods Data were collected on patient-reported demographics, voice-related diagnoses, voice-related handicap (Voice Handicap Index–10), likelihood of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…This study also demonstrated that, among those with voice problems in the last year, delay of care due to cost was more common among those without health insurance or with lower annual income levels. This is consistent with previous studies identifying concerns with cost of voice therapy as a barrier to seeking voice care . A survey of contemporary commercial music performers found that 37% indicated they do not seek help for vocal problems due to lack of adequate health coverage .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This study also demonstrated that, among those with voice problems in the last year, delay of care due to cost was more common among those without health insurance or with lower annual income levels. This is consistent with previous studies identifying concerns with cost of voice therapy as a barrier to seeking voice care . A survey of contemporary commercial music performers found that 37% indicated they do not seek help for vocal problems due to lack of adequate health coverage .…”
Section: Discussionsupporting
confidence: 90%
“…We could not find any studies in the literature that assessed the impact of race and ethnicity in adults with voice disorders. However, the voice disorder population has traditionally been described as predominantly white, wealthier, and educated . The difference in self‐reported voice outcomes among racial and ethnic groups may be secondary to cultural bias.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lack of follow-through could potentially be related to concerns that may be exacerbated by MH comorbidities, including unclear potential improvement, not understanding the purpose of therapy, or concerns that it would be too hard. 18 Insurance is another potential contributing factor because patients with both MH and voice diagnoses were more likely to have Medicaid. Although this was mitigated by inclusion of insurance status as a covariate in all regression analyses, it is possible there may be more subtle impacts that remain to be observed.…”
Section: Discussionmentioning
confidence: 99%